Superhydrophobic drug-loaded mesoporous silica nanoparticles capped with β-cyclodextrin for ultrasound image-guided combined antivascular and chemo-sonodynamic therapy. (February 2020) - Ho, Yi-Ju; Wu, Cheng-Han; Jin, Qiao-feng; Lin, Chih-Yu; Chiang, Pei-Hua; Wu, Nan; Fan, Ching-Hsiang; Yang, Chia-Min; Yeh, Chih-Kuang
Abstract: Interfacial nanobubbles (INBs) on a superhydrophobic surface has been proposed as a solid cavitation agent for enhancing inertial cavitation dose and ultrasound contrast imaging, but the dispersibility of superhydrophobic particles limits the biomedical application. For this study, we designed superhydrophobic mesoporous silica nanoparticles loaded with the anti-tumor drug Doxorubicin (FMSNs-Dox) for tumor therapy. The β-cyclodextrin was used to cap the superhydrophobic surface of FMSNs-Dox to reduce aggregation without inhibiting the accumulation of INBs. The mean size and a contact angle of FMSNs-Dox was 217 ± 58 nm and 129 ± 3°, respectively. The INBs cavitation on the surface of FMSNs-Dox during ultrasound sonication disrupted tumor vessels to allow a large amount of drug penetrating and trapping within tumors. The reduced tumor perfusion, histological reactive oxygen species staining, and tumor inhibition demonstrated that FMSNs-Dox sonication combined anti-vascular, sonodynamic and chemical therapies in a simple platform. Moreover, the repeatability of INB cavitation by single-injection FMSNs-Dox with multiple ultrasound sonication provided intratumoral ultrasound contrast-enhanced imaging from day 1–9 (enhancement of 3.84 ± 0.47 dB). Therefore, the characteristics of FMSNs-Dox with slow biodegradation and acoustic-sensitivity presented intratumoral day-scaled lifetime to provide a probability of repeated combination therapy by single-injection.